2018
DOI: 10.1111/eci.12902
|View full text |Cite
|
Sign up to set email alerts
|

PTH, vitamin D, and the FGF‐23–klotho axis and heart: Going beyond the confines of nephrology

Abstract: Background: Profound disturbances in mineral metabolism are closely linked to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 93 publications
(203 reference statements)
0
37
0
6
Order By: Relevance
“…FGF-23 is a bone-derived hormone in response to the increment of circulating phosphate and calcitriol levels, and its implication in the pathogenesis of CKD has been revealed that increased FGF-23 disrupts the bone-kidney-parathyroid hormone balance, which promotes the generation of hyperphosphatemia with the progression of CKD [ 18 ]. Recently, several clinical studies suggest that FGF-23, as a pro-inflammatory role, is involved in several aspects of cardiovascular diseases [ 8 , 10 , 19 , 20 ]. For example, FGF-23 is reported to be an independent factor for increased stage of peripheral vascular calcified atherosclerotic plaque and carotid artery intima-media thickness, and is responsible for the development and progression of atherosclerosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF-23 is a bone-derived hormone in response to the increment of circulating phosphate and calcitriol levels, and its implication in the pathogenesis of CKD has been revealed that increased FGF-23 disrupts the bone-kidney-parathyroid hormone balance, which promotes the generation of hyperphosphatemia with the progression of CKD [ 18 ]. Recently, several clinical studies suggest that FGF-23, as a pro-inflammatory role, is involved in several aspects of cardiovascular diseases [ 8 , 10 , 19 , 20 ]. For example, FGF-23 is reported to be an independent factor for increased stage of peripheral vascular calcified atherosclerotic plaque and carotid artery intima-media thickness, and is responsible for the development and progression of atherosclerosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor (FGF)-23, a member of FGF family, is an endocrine hormone correlates with calcium-phosphate homoeostasis, which is primarily expressed and secreted by osteocytes [7]. Initially, FGF-23 is reported to be implicated in the regulation of phosphatemia and mineral metabolism via interacting with its co-receptor klotho in kidney, and growing recent clinical evidences demonstrate the regulatory role of FGF-23 in diverse pathological processes of cardiovascular diseases (such as: coronary artery stenosis, myocardial fibrosis, cardiac injury, atherosclerosis, vascular calcification) and potential of FGF-23 as a clinical biomarker for predicting higher risk of adverse cardiovascular outcomes [8][9][10]. For example, FGF-23 is associated with accelerated plaque calcification as well as advanced severity of atherosclerosis in terms of vascular plaque burden, and it functions as a risk factor for coronary artery stenosis as well as adverse cardiovascular outcomes in CHD patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…PTH and CVR are directly correlated with such a correlation being consistently observed in studies involving both primary and secondary hyperparathyroidism [6, 7]. The underlying pathophysiology is in turn attributed to different mechanisms, from increased cardiac damage [8] to endothelial dysfunction [9]. At every age, pVitD and plasma PTH levels are inversely correlated, so that reduced levels of vitamin D can cause hyperparathyroidism and thus lead to an increased risk of cardiovascular events [5].…”
Section: Introductionmentioning
confidence: 94%
“…Both kidneys and heart share many mechanisms of homeostasis, and any injury to one can lead to one in the other. It is known that CaMKII is increased in many models of heart injury, and some models of CRS can cause arrhythmias and AP chances as well as contraction irregularities (Navarro-García et al, 2018;Alarcon et al, 2019). CaMKII could be crucial to the progression of CRS, more specifically related to the progression from acute HF to chronic (types 1 and 2).…”
Section: Camkii Inhibition Displays Cardioprotectionmentioning
confidence: 99%